Employment potential of the Volyn region: its content and importance in the conditions of market economy - Potapova, Alla; Lemekhova, Anastasiia (Human Geography Journal, 2017)
The concept of “employment potential” appeared in economics and media in 70’s and included in the scientific revolution in the 80’s of 20 century. The emergence of this concept was caused by the development of production, by formation of the economy and the use of human labor, which is an integral part of economic potential of the region. The employment potential is characterized by quantitative and qualitative sides. One сcomponent of the quantitative side is population which is one of the less numerous in Ukraine. However, over the last decade its population increased slightly, in contrast to most other regions of Ukraine. Qualitatively employment potential is sufficient but the increasing  number of schools of higher education III-IV accreditation levels due to commercialization leads to excess levels of educational professionals.Volyn region belongs to the first type from the five regional labor markets that are selected in Ukraine. Its features are well-defined labor depression in both the industrial and the agricultural sectors and forming an extreme conditions of reproduction of labor. Volyn region has low activities of labor potential usage. Due to irrational socio-economic policy of the government, it has been largely destroyed. The significant deskilling of the working population is an example. Essential disqualification of the working population, unemployment, mass emigration and destruction of vocational education occur as a result. The number of registered unemployed amounted to 11.4 thousand  people by end of September 2015. Six out of ten are women, 43.0 % of people live in rural areas and 79.9 % received unemployment benefits. Overall, the analysis of labor potential in the Volyn region showed that there are both positive and negative changes. The first one include the expansion of training and retraining in accordance with labor market needs; increasing employment in the modern sectors; reduced unemployment; improving the demographic situation;  negative trends like demographic and socio-economic nature reduce; number of specialists with higher education is growing.